A model for chromatin opening: stimulation of topoisomerase II and restriction enzyme cleavage of chromatin by distamycin. - Käs, E (1993)
Histone H1 preferentially and cooperatively binds scaffold-associated regions (SARs) in vitro via specific interactions with the numerous short A + T-rich tracts (A-tracts) contained in these sequences. Selective titration of A-tracts by the oligopeptide distamycin abolishes this interaction and results in a redistribution of H1. Similarly, treatment of intact cells and isolated nuclei with distamycin specifically enhances cleavage of internucleosomal linkers of SARs by topoisomerase II and restriction enzymes. The increased accessibility of these linkers is thought to result from the unfolding (or opening) of the chromatin fiber and to be due to a reduced occupancy by histone H1. Chromatin extraction and H1 assembly experiments support this view. We discuss a model whereby open, H1-depleted chromatin regions may be generated by titration of A-tracts by putative distamycin analogues; this local opening may spread to adjacent regions assuming highly cooperative H1-H1 interactions in chromatin.